2020
DOI: 10.3390/brainsci10120988
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and Overlapping Patterns of Acute Ethanol-Induced C-Fos Activation in Two Inbred Replicate Lines of Mice Selected for Drinking to High Blood Ethanol Concentrations

Abstract: The inbred high drinking in the dark (iHDID1 and iHDID2) strains are two replicate lines bred from the parent HS/Npt (HS) line for achieving binge levels of blood ethanol concentration (≥80 mg/dL BEC) in a four-hour period. In this work, we sought to evaluate differences in baseline and ethanol-induced c-Fos activation between the HS, iHDID1, and iHDID2 genetic lines in brain regions known to process the aversive properties of ethanol. Methods: Male and female HS, iHDID1, and iHDID2 mice underwent an IP saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 86 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…Because selective breeding principally changes the frequencies of genes affecting the targeted trait, any other differences between the selected line and its non-selected founder line may reflect coordinate genetic influences on the two traits. Thus, comparisons between HDID-1 and the founder HS/NPT lines have successfully been used to investigate the genetic and molecular determinants of high-risk drinking and identify potential pharmacotherapies for AUD ( Cozzoli et al, 2012 , 2016 ; Iancu et al, 2013 , 2018 ; Crabbe et al, 2017 , 2020 ; Ferguson et al, 2018 , 2019 ; Grigsby et al, 2020 ; Ozburn et al, 2020 ; Pozhidayeva et al, 2020 ; Robinson et al, 2020 ; Savarese et al, 2020 ). To test the effects of GR antagonism within this selectively bred line, HDID-1 mice were given both mifepristone, a non-selective steroid hormone receptor antagonist, and CORT113176, a specific GR antagonist.…”
Section: Introductionmentioning
confidence: 99%
“…Because selective breeding principally changes the frequencies of genes affecting the targeted trait, any other differences between the selected line and its non-selected founder line may reflect coordinate genetic influences on the two traits. Thus, comparisons between HDID-1 and the founder HS/NPT lines have successfully been used to investigate the genetic and molecular determinants of high-risk drinking and identify potential pharmacotherapies for AUD ( Cozzoli et al, 2012 , 2016 ; Iancu et al, 2013 , 2018 ; Crabbe et al, 2017 , 2020 ; Ferguson et al, 2018 , 2019 ; Grigsby et al, 2020 ; Ozburn et al, 2020 ; Pozhidayeva et al, 2020 ; Robinson et al, 2020 ; Savarese et al, 2020 ). To test the effects of GR antagonism within this selectively bred line, HDID-1 mice were given both mifepristone, a non-selective steroid hormone receptor antagonist, and CORT113176, a specific GR antagonist.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies should delineate the sex differences in the impact of silencing of CRF neurons on ethanol consumption (Schwandt et al, 2016). Previous reports show that G i/o -DREADDs in CRF neurons functionally inhibit the activity of CRF+ cells in vitro (Pleil et al, 2015), but herein, the function of G i/o -DREADDs in CRF neurons was analyzed using c-Fos, as previous studies have shown ethanol administration causes upregulation of c-Fos in the CeA (Leriche et al, 2008;McBride, 2002;Morales et al, 1998;Robinson et al, 2020). CNO administration prior to IP ethanol reduced the number of c-Fos+ cells within the CeA, suggesting that G i/o -DREADD activation inhibited CRF-neuronal activity stemming from an ethanol injection.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were given CNO 30 min prior to administration of 1.5 g/kg ethanol ip (13% v/v in 0.9% saline). This dose of ethanol has previously been indicated to increase c-Fos within the amygdala and simulates BECs comparable to those achieved within the DID paradigm (Marshall et al, 2015;McBride, 2002;Robinson et al, 2020). Two hours post ethanol injections, mice were euthanized via perfusion.…”
Section: Crf-cre C-fos Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Acute and chronic exposure to ethanol have been shown to activate the NTS as measured by c-Fos induction [16][17][18][19]. Activity within the NTS has been associated with substance use withdrawal [20]. Activation and inhibition of the NTS regulate both stress reactivity and alcohol consumption [4,12,13,21].…”
Section: Introductionmentioning
confidence: 99%